A sensor to acquire the relative movement between residual limb and prosthetic socket - Noll, Veronika; Weber, Paul; Scortecci, Stephanie; Beckerle, Philipp; Rinderknecht, Stephan (2016 IEEE International Conference on Systems, Man, and Cybernetics, SMC 2016 - Conference Proceedings, 2017)
This paper introduces a new approach to measuring relative movement between the residual limb and fitted prosthetic socket in an amputee during gait. Considering requirements motivated by the specific measurement task, a system for the recognition of residual limb movement within the socket system in dynamic gait situations is designed. To evaluate the feasibility of the measurement task with this sensor concept based on an optical 2D-motion sensor, a standalone functional model is established. The functional model is introduced regarding hardware and software components. This paper further presents preliminary experimental evaluation of the functional model. Results considering precision and accuracy of the functional model are displayed. Dependencies to movement velocity, overcome distance, and traveling direction are assessed. Depending on the parameters mentioned above, the realized prototype of the sensor concept shows relative errors regarding accuracy within the range of 2 to 6 %. Precision depends on movement direction as well as path lengths. Overall, the proposed sensor concept seems suitable for acquiring the relative movement between residual limb and prosthetic socket during amputee gait.
CRIS-Team Scopus Importer:2021-09-24